Awareness Regarding the Health Benefits of Millet and Its Consumption among the Population - Meenal Kulkarni; Purva Patil; Ajeet Saoji (Archives of Medicine and Health Sciences)
Background and Aim: Although there are national initiatives such as the National Mission for Sustainable Agriculture and the Millet Mission, there is a significant knowledge gap present among the people related to the importance and advantages of millets, inculcating their use in practice. Hence, the present study was conducted to assess the knowledge about the health benefits of millets and practices regarding its consumption and to determine the association between sociodemographic factors and the consumption of millets. Materials and Methods: Following institutional ethics committee approval, a semi-structured, pretested, prevalidated questionnaire was used to collect data via interviews of patients coming to the general outpatient department of a district hospital. Besides sociodemographic information, it also covered questions related to the participant’s knowledge and practices regarding the consumption of millets. Results: Only 23% of the participants had consumed any kind of millets. The most common reason for nonconsumption was the nonavailability of the millets followed by the family custom of not eating. Only 20.2% had moderate-to-good knowledge regarding the health benefits of millets. A statistically significant association was found between the consumption of millets and the type of family and level of education (P < 0.05). Conclusion: A significant knowledge gap was present among the population related to the health benefits of millets. The proportion of consumption of millets among the population was found to be low.